2020
DOI: 10.18203/2394-6040.ijcmph20203892
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate nursing students’ attitude towards online classes during lockdown period in India: imposed or interested?

Abstract: Background: Online classes were never been a part of regular habit in India. But due to corona pandemic every institute is offering online classes whether medical or nursing institutes. Aim was to ascertain the attitude towards online classes among undergraduate nursing students during lockdown period.Methods: This cross-sectional descriptive survey was conducted on 394 undergraduate nursing students in which samples were chosen through convenient sampling technique. A valid and reliable self-structured questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 10 publications
3
15
1
Order By: Relevance
“…These findings are in correspondence with the findings of some previous studies. [5][6][7][8]9,12 In contrast to the present finding studies conducted in India. 6,14 The proportion of the respondent's study in higher classes such as graduation and 51% 49%…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…These findings are in correspondence with the findings of some previous studies. [5][6][7][8]9,12 In contrast to the present finding studies conducted in India. 6,14 The proportion of the respondent's study in higher classes such as graduation and 51% 49%…”
Section: Discussioncontrasting
confidence: 63%
“…These findings are similar to the findings of previous studies conducted in India and other countries. [5][6][7][8][9] The percentage of male respondents (57%) was comparatively high than female respondents (47%). These findings are in correspondence with the findings of some previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It makes sense that the reactions to change are also complicated and often contradictory because the change in itself can be overwhelming and multifaceted (Oreg and Sverdlik 2011). Similarly, a study conducted in India during the lockdown period among nursing students reported unfavourable attitudes towards online classes (Gaur et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 virus spreads primarily through droplets of saliva or discharge from the nose when an infected person coughs or sneezes, so it's important that you also practice respiratory etiquette (for example, by coughing into a flexed elbow). 5,6 Knowledge is a familiarity, awareness, or understanding of someone or something, such as facts, information, descriptions, or skills, which is acquired through experience or education by perceiving, discovering, or learning. Knowledge can refer to a theoretical or practical understanding of a subject.…”
mentioning
confidence: 99%